Anatomical study of the iliohypogastric, ilioinguinal, and genitofemoral nerves using high‐resolution ultrasound. Issue 1 (January 2015) - Tagliafico, Alberto; Bignotti, Bianca; Cadoni, Angela; Perez, Maribel Miguel; Martinoli, Carlo
ABSTRACT Introduction: In this study we aimed to determine whether high‐resolution ultrasound (US) can identify the iliohypogastric (IH), ilioinguinal (II), and genitofemoral (GF) nerves and their relations. Methods: This investigation, initially undertaken in cadavers, was followed by a high‐resolution US study in 30 healthy adult volunteers (180 nerves) by 2 musculoskeletal radiologists on separate occasions, using 2 different approaches (proximal to distal and distal to proximal). A 0–3 scale was used to assess nerve visibility. Location and course of the IH, II, and GF nerves and their relations to adjacent anatomical structures were analyzed. Results: Nerves and their terminal branches were better visualized with the distal‐to‐proximal approach (P < 0.05). Visualization of the terminal branches was possible in up to 60% of volunteers. Conclusions: High‐resolution ultrasound (US) can identify the IH, II, and GF nerves at the level of the abdominal wall and the terminal branches in the majority of volunteers. Muscle Nerve51: 42–48, 2015